Profile of patients referred for computed tomography, likely to be explored by scintigraphy imaging in a country with no nuclear medicine service: The case of Togo - Adambounou, Kokou; Gurhajahabiri, Pascal S; Houndetoungan, Gilles David; ADIGO, A. M. Yao; KLUYIBO, Komi; SODOGAS, Fabrice (My University, 2022)
Introduction: Describe the profile of patients referred for computed tomography (CT) likely to be scanned with scintigraphy imaging in Togo. Methods: Prospective study carried out from May 15 to August 15 2020 including patients referred for non-traumatic CT scans (excluding strokes) in all the radiology centres in Togo with operational CT scans. The good practice guide of the French Societies of Radiology (SFR) and Nuclear Medicine (SFMN) was used as a reference for case selection. Results: A total of 328 patients, representing 14.6% of those referred for non-traumatic CT scans (excluding strokes) were concerned. The sex ratio was 0.74 and the average age 50.58 ± 19.02 years. The patients had a health insurance in 50% of cases and were civil servants in 62.5% of cases. They mainly came from the cardiology (6.7%) and oncology departments (6.1%). Most common explorations were chest-abdomen-pelvis CT scans (36.3%) and thorax angiography CT (22.9%). Pulmonary embolism (24.1%), breast and prostate cancer extension assessment (18.3%) were the most frequent indications. Scintigraphy was indicated mainly (85.37%) as a second line of exploration. The most concerned fields of nuclear medicine were nuclear oncology (26.2%), cardio-pneumology (25%) and nuclear neurology (20.1%). Scintigraphy imaging was of a better or the same grade of recommendation as CT scan in 53.7% of cases, and of a lower or the same dose class as CT scan in 90.2% of cases. Conclusion: A significant number of patients referred for CT scans in Togo were likely to be explored by scintigraphy imaging, hence the need to create a nuclear medicine department there.
Keywords: Scintigraphy imaging; Nuclear medicine; Computed tomography; Radiation protection; Togo